INOVASI PEMBELAJARAN MATEMATIKA: PENGGUNAAN MEDIA PEMBELAJARAN BERBANTUAN CANVA MATERI TRANSFORMASI GEOMETRI REFLEKSI DI SMP NEGERI 1 TELAGA BIRU - Harun, Artika Rahayu; Yahya, Lailany; Katili, Nancy; Ismail, Sumarno (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study is a development study that uses the 4-D model (define, design, develop, desiminate). Where the results of this study are learning media that can help students understand the material, especially on reflection material. The media developed is Canva media which has passed the validation stage of the readability test and the product cona test until Canva media can be said to be feasible as a learning media that can be distributed to students. The research location is SMP Negeri 1 Telaga Biru, where this media was developed there due to the lack of limited use of learning media and students tend to be taught using books in the absence of other learning resources. This attracted researchers to conduct research at the school. based on the results of the study, the Canva reflection media that has been developed gets a positive response from teachers and students with a teacher response of 100% and students 95%